2001
DOI: 10.1038/sj.bjp.0703829
|View full text |Cite
|
Sign up to set email alerts
|

Improved diabetic syndrome in C57BL/KsJ‐db/db mice by oral administration of the Na+‐glucose cotransporter inhibitor T‐1095

Abstract: 1 The therapeutic e ects of an orally active inhibitor of Na + -glucose cotransporter (SGLT), T-1095 (a derivative of phlorizin; 3-(benzo [b]furan-5-yl)-2',6'-dihydroxy-4'-methylpropiophenone 2'-O-(6-O-methoxycarbonyl-b-D-glycopyranoside)) were examined in C57BL/KsJ-db/db (db/db) mice, a genetic animal model of obese type 2 diabetes. 2 The higher renal SGLT activity in db/db mice than normoglycaemic C57BL/KsJ-db/+m (db/ +m) mice may support the rationale for using an SGLT inhibitor in the treatment regimen for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
110
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 43 publications
(39 reference statements)
11
110
1
Order By: Relevance
“…Two weeks of treatment with dapagliflozin improved glucose utilization and was accompanied by reduced glucose production and enhanced glucose influx into liver tissue, but the treatment showed no effect on glucose uptake in skeletal muscle and adipose tissue [13] . Similar results have been described for other SGLT-2 inhibitors, for example, T-1095 and empagliflozin [14,15] . Gluco-or lipotoxicity contributes to the decline of β-cell function and mass [16] .…”
Section: Acta Pharmacologica Sinica Npgsupporting
confidence: 74%
See 1 more Smart Citation
“…Two weeks of treatment with dapagliflozin improved glucose utilization and was accompanied by reduced glucose production and enhanced glucose influx into liver tissue, but the treatment showed no effect on glucose uptake in skeletal muscle and adipose tissue [13] . Similar results have been described for other SGLT-2 inhibitors, for example, T-1095 and empagliflozin [14,15] . Gluco-or lipotoxicity contributes to the decline of β-cell function and mass [16] .…”
Section: Acta Pharmacologica Sinica Npgsupporting
confidence: 74%
“…As the first rate-limiting step in skeletal muscle glucose metabolism, glucose uptake is markedly impaired under diabetic conditions [33] . A few studies have demonstrated that long-term treatment with SGLT2 inhibitors could enhance insulin sensitivity in the livers of type 2 diabetic animal models, but did not effect insulin sensitivity in muscle and adipose tissue [13][14][15] . In this study, a significant decrease in serum insulin levels www.chinaphar.com Yan PK et al Acta Pharmacologica Sinica npg was observed after chronic treatment with SHR3824 that was accompanied by decreased fasting blood glucose and HbA1c levels, suggesting that whole-body insulin sensitivity was improved.…”
Section: Discussionmentioning
confidence: 99%
“…In Akita and streptozotocin-induced animal models of insulin-deficient diabetes, SGLT2 inhibition reduced albuminuria [18][19][20]. SGLT2 inhibition has similar anti-albuminuric effects in animal models of type 2 diabetes [21], including recent evidence that empagliflozin reduced albuminuria, independent of effects on BP or hyperglycaemia, in BTBR ob/ob mouse models of type 2 diabetes [22]. Previous clinical studies in type 2 diabetes patients with and without CKD have shown that SGLT2 inhibition is associated with an acute but modest decline in eGFR within 3-6 weeks of treatment initiation, followed by a period of stable renal function for 52-104 weeks; this change is reversible after drug cessation for 2 weeks [17,23,24].…”
Section: Discussionmentioning
confidence: 81%
“…There are already examples of the clinical use of glucose transporter inhibitors. An oral inhibitor of sodium-glucose cotransporters, T-1095, has been administered to diabetic mice (Arakawa et al, 2001). Higher levels of these transporters are present in the kidneys of diabetic mice than in normal mice and treatment with the inhibitor decreased blood glucose levels by promoting glycosuria.…”
Section: Implications and Conclusionmentioning
confidence: 99%